Comparative Analysis of the Chloroplast Genome for Aconitum Species: Genome Structure and Phylogenetic Relationships - Xia, Conglong; Wang, Manjiong; Guan, Yunhui; Li, Jian (Frontiers in Genetics, 2022)
Aconitum is an important medicinal group of the Ranunculaceae family and has been used as conventional medicine in Bai, Yi, and other ethnic groups of China. There are about 350 Aconitum species globally and about 170 species in China. It is challenging to identify the species in morphology, and the lack of molecular biology information hinders the identification and rational utilization of the germplasm of this genus. It is, therefore, important to find a better method to distinguish these species. This paper acquired the complete chloroplast (CP) genome sequence of ten medicinal plants of Aconitum species from Yunnan by Illumina paired-end (PE) sequencing technology and compared it with other species in the same family and genus. These CP genomes exhibited typical circular quadripartite structure, and their sizes ranged from 155,475 (A. stylosum) to 155,921 bp (A. vilmoinianum), including a large single-copy region (LSC), a small single-copy region (SSC), and two inverted repeat regions (IRS). Their gene content, order, and GC content (38.1%) were similar. Moreover, their number of genes ranged from 129 (A. vilmoinianum) to 132 (A. ramulosum), including 83 to 85 protein-coding genes (PCGs), 37 tRNA genes (tRNAs), eight rRNA genes (rRNAs), and two pseudogenes. A total of 60 to 70 simple sequence repeats (SSRs) and 22 to 60 long repeat sequences were identified. IR regions showed higher variability than the SSC region and LSC region. Nine mutational hotspots were screened out, trnK-UUU-trnQ-UGG, trnS-GCU-trnGCC, trnE-UUC-trnT-GGU, trnT-UGU-trnL-UAA, trnV-UAC, rps18, rpl16-rps3, ccsA, and ndhD respectively. The phylogenetic tree of ten Aconitum spp. and other related species revealed that the whole CP genome could be used as a super-barcode to identify these Aconitum species. This study provides a potential molecular marker and genomic resource for phylogeny and species identification of Aconitum species and an important reference and basis for Ranunculaceae species identification and phylogeny.